MIR497HG‐Derived miR‐195 and miR‐497 Mediate Tamoxifen Resistance via PI3K/AKT Signaling in Breast Cancer - Yao Tian; Zhao‐Hui Chen; Peng Wu; Di Zhang; Yue Ma; Xiao‐Feng Liu; Xin Wang; Dan Ding; Xu‐Chen Cao; Yue Yu (Advanced Science, 2023)
Abstract Tamoxifen is commonly used for the treatment of patients with estrogen receptor‐positive (ER+) breast cancer, but the acquired resistance to tamoxifen presents a critical challenge of breast cancer therapeutics. Recently, long noncoding RNA MIR497HG and its embedded miR‐497 and miR‐195 are proved to play significant roles in many types of human cancers, but their roles in tamoxifen‐resistant breast cancer remain unknown. The results indicate that MIR497HG deficiency induces breast cancer progression and tamoxifen resistance by inducing downregulation of miR‐497/195. miR‐497/195 coordinately represses five positive PI3K‐AKT regulators (MAP2K1, AKT3, BCL2, RAF1, and CCND1), resulting in inhibition of PI3K‐AKT signaling, and PI3K‐AKT inhibition in tamoxifen‐resistant cells restored tamoxifen responsiveness. Furthermore, ER α binds the MIR497HG promoter to activate its transcription in an estrogen‐dependent manner. ZEB1 interacts with HDAC1/2 and DNMT3B at the MIR497HG promoter, resulting in promoter hypermethylation and histone deacetylation. The findings reveal that ZEB1‐induced MIR497HG depletion contributes to breast cancer progression and tamoxifen resistance through PI3K‐AKT signaling. MIR497HG can be used as a biomarker for predicting tamoxifen sensitivity in patients with ER+ breast cancer.